THE EFFECT OF THE PROBLEM BASED LEARNING MODEL ON MATHEMATICAL PROBLEM-SOLVING ABILITY - Zulkarnain, Ihwan (Tesseract: International Journal of Geometry and Applied Mathematics, 2024)
This research aims to determine the effect of the Problem Based Learning (PBL) learning model on students' mathematical problem-solving abilities. The research method used is a quasi-experimental method. The sampling technique uses simple random sampling technique. The instrument in this research was a test of mathematical problem-solving ability in the form of an essay with 10 questions. Data analysis techniques were carried out using correlation tests and simple regression tests. The results of the research show that 1) there is a positive influence of the Problem Based Learning learning model on the mathematical problem solving abilities of students at SMK Putra Pelita Tenjolaya 2) the average value of students' mathematical problem solving abilities on the main material of the Linear Program which is taught using the Problem Based Learning learning model (PBL) is greater than the average value of students' mathematical problem solving abilities who use the Expository learning model.